ChemInform Abstract: A Facile One‐Pot Route for the General Synthesis of Triazole Linked Chiral 2‐Substituted Benzimidazoles. Issue 47 (4th November 2013) - Dutta, Samrat; Sarkar, Swarbhanu; Sen, Asish Kumar
Abstract The fast and plain approach involves copper(I) catalyzed simultaneous formation of benzimidazole and triazole rings.